O enfrentamento ao trabalho da criança e do adolescente: uma avaliação política do Programa de Erradicação do Trabalho Infantil no Brasil - VASCONCELOS, Maria das Graças de Oliveira (2019)
This work has child and juvenile labor as its theme, having as empirical reference the Program of Eradication of Child Labor (PETI), considered as the materialization of state intervention in the issue, which is the object of study. The Program was created in 1996 under the strong influence of international organizations to eliminate children’s work and as a reflection of the movement for the redemocratization of the Brazilian society in the late 1980s, which called for social rights including the defense of full protection of children and teenagers from the country. Child labor, characterized as a multifaceted phenomenon, has wide repercussions for the lives of children and adolescents, being one of the most perverse violations of rights. This is an evaluative research of public policies, in the field of Applied Social Sciences, under the political evaluation modality of the program. Its general objective was to develop an evaluation of PETI, considering the three dimensions provided for in this modality: the political, economic and social determinants that conditioned the process of its formulation; the central ethical-political principles that underlie the Program and, finally, the analysis of the consistency and internal coherence of its design and engineering, privileging the management and co-financing model, two basic mechanisms of a public policy. With a qualitative approach, we used bibliographic research, documentary research, as well as secondary data analysis. From the deepening in the genesis of the phenomenon, in the light of the historical materialism method, its relationship with the capitalist mode of production is evidenced, being the child labor functional to the capital. Among the main results of the study, it was identified that the program design has a link with neoliberal ideas. By adopting the focus within its reach, it violates the principle of absolute priority in which children and adolescents must be fully met by public policies, and the Program, in this sense, is far from the perspective of rights and social justice. Moreover, the elements of its engineering, specifically the eligibility and permanence criteria in the program, are exclusionary and limiting to the purpose of preventing and eradicating child labor.